2011
DOI: 10.1017/s1751731110002028
|View full text |Cite
|
Sign up to set email alerts
|

Red clover polyphenol oxidase and lipid metabolism

Abstract: Increasing the polyunsaturated fatty acid (PUFA) composition of milk is acknowledged to be of benefit to consumer health. Despite the high PUFA content of forages, milk fat contains only about 3% of PUFA and only about 0.5% of n-3 fatty acids. This is mainly due to intensive lipid metabolism in the rumen (lipolysis and biohydrogenation) and during conservation (lipolysis and oxidation) such as drying (hay) and ensiling (silage). In red clover, polyphenol oxidase (PPO) has been suggested to protect lipids again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 48 publications
(93 reference statements)
3
56
0
1
Order By: Relevance
“…The binding of proteins to phenols, which results from PPO activity, lead to inhibition of lipolysis in the silage and as lipolysis is a prerequisite for biohydrogenation of PUFAs in the rumen, the extent of biohydrogenation is decreased. However, Van Ranst et al (2011) concluded that the importance of this inhibition of lipolysis in the silage is questionable. The PPO-mediated inhibition of lipolysis failed to protect lipids against microbial lipases, which become important during later stages of ensiling and in the rumen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding of proteins to phenols, which results from PPO activity, lead to inhibition of lipolysis in the silage and as lipolysis is a prerequisite for biohydrogenation of PUFAs in the rumen, the extent of biohydrogenation is decreased. However, Van Ranst et al (2011) concluded that the importance of this inhibition of lipolysis in the silage is questionable. The PPO-mediated inhibition of lipolysis failed to protect lipids against microbial lipases, which become important during later stages of ensiling and in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…The PPO-mediated inhibition of lipolysis failed to protect lipids against microbial lipases, which become important during later stages of ensiling and in the rumen. Instead, Van Ranst et al (2011) postulated that PUFA could be protected against metabolism through encapsulation in protein-phenol complexes. In the current paper, there were, however, no significant effects on apparent recoveries of PUFA from RC-G compared with the grass silages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other differences between grasses must be acknowledged, the results are not indicative of a PPO protective response in grass. There is little doubt that PPO in both red clover and grasses can deactivate lipase activity (Lee et al, 2006b;Van Ranst et al, 2011). However, for PPO to protect lipid in the ruminal environment, there appears to be a requirement for the lipid to be complexed within PBP, which would limit microbial lipase access to the PUFA-glycerol ester bond ).…”
Section: Fatty Acid Metabolism Across the Rumenmentioning
confidence: 99%
“…A further benefit of red clover silage is a reduction in C18 PUFA biohydrogenation compared to grass silage (Lee et al, 2003). Polyphenol oxidase reduces plant mediated lipolysis (Lee et al, 2004) by inhibiting plant lipases (Van Ranst et al, 2011).…”
Section: Introductionmentioning
confidence: 99%